1958
DOI: 10.1002/j.2050-0416.1958.tb06309.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Studies of Embryo and Endosperm

Abstract: Resultsof chemical analyses of wheat germ and of barley endosperm indicate that, while the germ preparation can yield typical pectic materials, including a pure araban, such materials are absent from the central endosperm. The behaviour of sections of seeds of various grasses in a number of different solvents indicates that in all samples examined of Bromus sterilis, and in some samples of barley, intercellular cementing material is either lacking or else very readily soluble in water, whereas in all samples e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1961
1961
1988
1988

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Pectin has not been detected in water extracts of wheat (Preece & Hobkirk, 1953;MacLeod & McCorquodale, 1958) or in wheat endosperm cell walls (Mares & Stone, 1973a), but it is conceivable that the arabinogalactan-peptide could be functionally equivalent to the neutral arabinogalactan which is frequently extracted in the pectic fraction of other plant tissues. Ginzburg (1958) andMacLeod &McCorquodale (1958) have reported the presence of protein in the middle lamella of some plant cells, which suggests the possibility that arabinogalactanpeptide could be a component of the middle lamella in mature endosperm. At present it remains uncertain whether the arabinogalactan-peptide is associated with endosperm cell walls or is a cytoplasmic component, and detailed information as to its subcellular localization will be necessary before a functional role can be ascribed to this molecule.…”
Section: Discussionmentioning
confidence: 99%
“…Pectin has not been detected in water extracts of wheat (Preece & Hobkirk, 1953;MacLeod & McCorquodale, 1958) or in wheat endosperm cell walls (Mares & Stone, 1973a), but it is conceivable that the arabinogalactan-peptide could be functionally equivalent to the neutral arabinogalactan which is frequently extracted in the pectic fraction of other plant tissues. Ginzburg (1958) andMacLeod &McCorquodale (1958) have reported the presence of protein in the middle lamella of some plant cells, which suggests the possibility that arabinogalactanpeptide could be a component of the middle lamella in mature endosperm. At present it remains uncertain whether the arabinogalactan-peptide is associated with endosperm cell walls or is a cytoplasmic component, and detailed information as to its subcellular localization will be necessary before a functional role can be ascribed to this molecule.…”
Section: Discussionmentioning
confidence: 99%
“…In malting barley, pectinase and polygalactuoironase were found in the malt, in the endosperm, and in the embryo and were considered to be produced by the scutellum (Harris, 1962;Briggs, 1973). Since it is evident that, except in rice, no pectins occur in the starchy endosperm or in the aleurone (Bacic & Stone, 1981;Fincher & Stone, 1981;MacLeod & McCorquodale, 1958;Mares & Stone, 1973a, b;McNeil et al, 1975) it is suggested here that the role of the scutellar pectinase is to hydrolyse the anticlinal middle lamellae of the epithelial cells, hydrolysis being a prerequisite for their elongation as papillae. Swift & O'Brien (1972b) emphasized that none of the cytological changes observed by them in the epithelial and parenchyma of the wheat scutellum sheds "light on the processes of nutrient absorption or secretion of diastase".…”
Section: The Fine Structure Of the Epitheliummentioning
confidence: 89%
“…In wheat, these cells are arranged radially from the center (Bessey, 1894). Their walls are reported to lack pectin and to be held together instead by proteinaceous material (MacLeod and McCorquodale, 1958). Endosperm cells are so gorged with food reserves that the nucleus sometimes appears crushed.…”
Section: Storage Cellsmentioning
confidence: 99%